”Jag är bara här”: Humanvetenskaperna, klimataktivismen och apatin som möjlighet - Johansson, Sven Anders (K&K - Kultur og Klasse, 2024)
The article takes as its starting point Leo Tolstoy’s character Pierre Bezukhov. His passive presence at the battle of Borodino, in Tolstoy’s War and Peace, is contrasted with today’s climate activism, exemplified by the Swedish human ecologist Andreas Malm. In his book How to Blow up a Pipeline, Malm argues that global warming forces scientists and scholars to become activists, and activists to turn to violence. This analysis, the article argues, is based on a simplistic notion of action (”one acts or one does not”) and a strong conviction of being right. If this certitude is problematic, it is also typical of our time. Where, then, does this tendency to simplify the complicated, and replace all uncertainty with sureness, come from? One answer is that activism requires determination, which in its turn presupposes access to the truth. Another explanation lies in the binary operations of the digital media we all rely upon. At the most basic level, these operations exclude all approximation, all nuances, all doubt: the options are one or zero. Against this background, it becomes crucial to defend a research practice that refrains from simplifications. In Sloterdijk, the article finds an argument for interrupting the affective impulses that reach us constantly. From Popper, it fetches an understanding of research as an event. Via Marx’s well-known formulation that philosophers must change the world, not just interpret it, the text then moves to Adorno’s defense of theoretical thinking. The question is, however, whether critical theory has any edge left. Has it not just become a part of the academic apparatus it once reacted against? The article finds an answer in Lyotard, and his idea of a theoretical apathy. This idea reminds a lot of the starting point of the article: Pierre Bezukhov’s comic but clear-sighted passivity on the battlefield.